2014
DOI: 10.1111/1440-1630.12156
|View full text |Cite
|
Sign up to set email alerts
|

Understanding home modifications impact on clients and their family's experience of home: A qualitative study

Abstract: The negative outcomes and poor consultation experiences suggest the need for occupational therapists to understand their client's personal experience of home and to comprehensively follow-up and evaluate these following home modifications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 26 publications
3
42
0
Order By: Relevance
“…The importance of the therapeutic relationship (Palmadottir, 2006); the use of active listening skills (Turner et al, 2000); the need to understand the person with lived experience as an expert in their own needs and collaborating with them in decision making (Aplin, Jonge, & Gustafsson, 2015); and exposure to people with lived experience throughout curriculum design and delivery (Repper & Breeze, 2007) have been highlighted. The importance of the therapeutic relationship (Palmadottir, 2006); the use of active listening skills (Turner et al, 2000); the need to understand the person with lived experience as an expert in their own needs and collaborating with them in decision making (Aplin, Jonge, & Gustafsson, 2015); and exposure to people with lived experience throughout curriculum design and delivery (Repper & Breeze, 2007) have been highlighted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of the therapeutic relationship (Palmadottir, 2006); the use of active listening skills (Turner et al, 2000); the need to understand the person with lived experience as an expert in their own needs and collaborating with them in decision making (Aplin, Jonge, & Gustafsson, 2015); and exposure to people with lived experience throughout curriculum design and delivery (Repper & Breeze, 2007) have been highlighted. The importance of the therapeutic relationship (Palmadottir, 2006); the use of active listening skills (Turner et al, 2000); the need to understand the person with lived experience as an expert in their own needs and collaborating with them in decision making (Aplin, Jonge, & Gustafsson, 2015); and exposure to people with lived experience throughout curriculum design and delivery (Repper & Breeze, 2007) have been highlighted.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of person-centred practice identified by participants in this study has been documented previously in other research. The importance of the therapeutic relationship (Palmadottir, 2006); the use of active listening skills (Turner et al, 2000); the need to understand the person with lived experience as an expert in their own needs and collaborating with them in decision making (Aplin, Jonge, & Gustafsson, 2015); and exposure to people with lived experience throughout curriculum design and delivery (Repper & Breeze, 2007) have been highlighted. It is recommended that there is greater and more equal inclusion of people with lived experience of disability in design and delivery of curriculum through attendance at curriculum planning days, input into writing scenarios, and participation in teaching sessions such as communication skills workshops.…”
Section: Discussionmentioning
confidence: 99%
“…The DOHM's construct of interest was the home environment. Six dimensions of the home environment were determined through a literature review and qualitative study involving home modification clients and their families (Aplin, ; Aplin, de Jonge & Gustafsson, ; Aplin et al ., ). These dimensions included the personal, social, physical, temporal, occupational and societal dimensions.…”
Section: Introductionmentioning
confidence: 97%
“…These wider outcomes point to the aspects of the home environment, which are important to consider during the home modification process, and highlight the impact of modifications on clients' experience of home. Experience of home is defined as ‘one's individual experience of their home environment including its meaning and usability’ (Aplin, de Jonge & Gustafsson, , p. 123). While the outcomes of home modification on the experience of home have been widely described as shown above, these have largely been obtained from qualitative approaches (Heywood, ,b, ; Jones et al ., ; Mayes et al ., ; Roy et al ., ; Tanner et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was shown that health risks related to caregiving, such as back pain, were in some cases prevented by home modifications and 48% of the family caregivers mentioned that mental and physical strain was reduced [23]. Two qualitative studies from Australia on home modifications included the perspective of cohabitants and families and showed that home modifications increased applicants' independence, resulting in some of them no longer having to rely on others, and also resulting in the role of the caregiver and the activities of the caregiver becoming easier following the home modification [20,24]. Whether these indications of positive effects on caregiving for cohabitants are true also regarding housing adaptations are not known.…”
Section: Introductionmentioning
confidence: 99%